Hydrogen production using piston reactor technology: Process design and integration for CO2 emission reduction - Mary Katebah (17380462) (2022)
The piston reactor is emerging as a simple, inexpensive, and compact technology to carry out chemical reactions. Potential piston reactor advantages include high temperature and pressure conditions at short residence times, large throughput, and fast quenching steps. Published research related to hydrogen production using piston reactors has almost exclusively focused on the POX route for hydrogen production and on exploring reactor performance as opposed to overall process performance in terms of specific production costs and emissions. This study provides a process-level understanding of the techno-economics of hydrogen production using piston reactor technology via the three prominent routes for grey and blue hydrogen production: methane partial oxidation (POX), auto-thermal reforming (ATR), and steam methane reforming (SMR). A piston reactor model is initially used to screen the reactor performance in terms of methane conversion and hydrogen production, revealing underperformance for the SMR route. Next, stand-alone hydrogen production processes embedding the piston reactors for the remaining POX and ATR routes are synthesized and specific production costs and CO2 emissions for ‘grey’ hydrogen production determined. Next, the piston reactor processes are integrated with CO2 capture and compression steps for subsequent sequestration and the impact of such CO2 emission mitigation on ‘blue’ hydrogen production costs is evaluated. The obtained results show that the piston-reactor ATR process significantly outperforms the piston-reactor POX process for both grey and blue hydrogen production. For a 100 TPD plant capacity and a natural gas price of $3.3/GJ, blue hydrogen production costs for the piston reactor-based ATR processes are observed to be 1.6/kg H2, which is competitive with reported blue hydrogen production costs using the conventional SMR route. A sensitivity study reveals that the plant capacity has significant impact while piston reactor useful life had low impact hydrogen production costs. Other Information Published in: Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.energy.2022.124999